Relational Exchange Mechanisms and Domestic Travel Continuity Intentions: Evidence from Thailand’s Tourism Recovery Period - Sumana Suttipun (Advances in Tourism Studies, 2025)
This study examines domestic travel continuity intention during Thailand’s tourism recovery period through a relational exchange framework grounded in social exchange theory. Drawing on survey data from 500 domestic travelers, structural equation modeling was employed to test the relationships among travel motivation, tourist trust, tourist loyalty, and continuity intention. The findings reveal that travel motivation positively influences trust, loyalty, and continuity intention. Tourist trust strengthens loyalty and directly enhances continuity intention, while loyalty emerges as the strongest predictor of sustained domestic travel behavior. Mediation analysis confirms that loyalty partially mediates the relationship between trust and continuity intention, and that trust and loyalty sequentially mediate the relationship between motivation and continuity intention. The results reconceptualize continuity intention as a relational outcome shaped by layered exchange mechanisms rather than a purely motivational response. The study contributes to tourism recovery literature by providing a mechanism based explanation of domestic tourism resilience in post crisis environments.